2020
DOI: 10.21873/anticanres.14314
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Adjuvant Combination Therapy With Trastuzumab and Chemotherapy in HER2-positive Early Breast Cancer: A Single Institutional Cohort Study from Clinical Practice

Abstract: The rates of relapse-free and distant metastasis-free survival were significantly better in cohort B than in cohort A. The risk factors of distant recurrence found in cohort A, such as the presence of lymph node metastasis, lymphatic invasion, and a low histological grade, did not increase the risk in cohort B. Conclusion: Many risk factors seemed to have been negated by adjuvant trastuzumab administration. Therefore, further escalation of adjuvant treatment should be carefully considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…In the current study, the OS benefits were similar in both the matched neoadjuvant cases and adjuvant controls who also underwent targeted therapy. A previous study suggested that neoadjuvant chemotherapy is the preferred treatment strategy for patients with TNBC and HER2-enriched breast cancer ( 26 ), and the addition of an anti-HER2 regimen in both adjuvant and neoadjuvant settings can lead to favorable survival outcomes ( 27 29 ). However, in the present study, the treatment benefits of chemotherapy in both adjuvant and neoadjuvant settings were not observed in the patients with luminal A breast cancer following matching, which contrasts with the findings of a previous study ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, the OS benefits were similar in both the matched neoadjuvant cases and adjuvant controls who also underwent targeted therapy. A previous study suggested that neoadjuvant chemotherapy is the preferred treatment strategy for patients with TNBC and HER2-enriched breast cancer ( 26 ), and the addition of an anti-HER2 regimen in both adjuvant and neoadjuvant settings can lead to favorable survival outcomes ( 27 29 ). However, in the present study, the treatment benefits of chemotherapy in both adjuvant and neoadjuvant settings were not observed in the patients with luminal A breast cancer following matching, which contrasts with the findings of a previous study ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…This highlights the importance of further investigation of HER2 in OSCC development. Currently, small molecule inhibitors or antibodies targeting HER2 have been approved for treatment of patients with HER2-positive breast cancer, non-small cell lung cancer (NSCLC), and gastroesophageal cancer (Iqbal and Iqbal, 2014;Cameron et al, 2017;Kneissl et al, 2017;Liu et al, 2018;Okamoto et al, 2020). Two FDA-approved HER2 monoclonal antibodies (mAbs), namely trastuzumab, and pertuzumab, have shown antitumor effects by attacking HER2 signaling (Gerson et al, 2017).…”
Section: Introductionmentioning
confidence: 99%